PERAN DISDUKCAPIL KABUPATEN CIAMIS MELALUI PROGRAM SILANCAR DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Gina Mardiana; Arie Budiawan; Ii Sujai (JOURNAL SAINS STUDENT RESEARCH, 2025)
To provide faster, safer, and friendlier population administration services to the community, the Ciamis District Population and Civil Registration Office launched an innovation through the Quick, Safe, and Friendly Service System program (Silancar). This study aims to analyze the role of the Ciamis Disdukcapil through the Silancar program in improving the quality of public services, as well as to identify various constraints and challenges that arise during its implementation process. This research uses a qualitative method with a descriptive approach. Data collection was carried out through interviews, direct observation, and documentation techniques. The theoretical approach used refers to the role of the Government according to Sondang P. Siagian, which includes roles as Stabilisator, innovator, modernizer, pioneer, and executor. The results of the study show that the implementation of the Silancar program has been carried out but has not yet fully reached the optimal level. Several indicators of the government's role still show weaknesses, particularly in the availability of technological infrastructure, the effectiveness of socialization, and the role as a role model for institutions. Several technical constraints such as unstable internet connections, limited number of computer devices, and the low digital literacy of the community also hinder the effectiveness of online services. To achieve this, the development of infrastructure, technology education, and a more intensive socialization approach is required. With the strengthening of institutional roles and collaboration among stakeholders, the online service program has the potential to become an inclusive, efficient, and sustainable digital service to support the improvement of the quality of civil registration services in Ciamis Regency.